Ferromagnetic resonance of quasiperiodic Au/Co Fibonacci multilayers: Magnetic anisotropy and interlayer coupling - Sousa M.A. (2019)
Ferromagnetic resonance (FMR) study of quasiperiodic Au/Co Fibonacci multilayers revealed that uniform resonance modes related to the bulk Co and interface Au/Co regions of Co layers were excited in all multilayers. Paramagnetic and spin-wave resonance (SWR) modes also were observed into multilayers associated to higher order Fibonacci sequence. The FMR results show that there is no direct correlation between the number of absorption modes and the number of magnetic layers or the Fibonacci generation sequence of the quasiperiodic structure. Analysis of SWR modes revealed an interlayer effective coupling constant higher than that known for conventional Au/Co multilayers.